(untitled) (American Journal of Technology and Applied Sciences, 2025)
This paper presents a numerical modeling approach to analyze the characteristics of a field-effect transistor (FET) with a quantum dot array channel. The study primarily considers the quantum size distribution, gamma distribution as a function of density, and the resulting energy distributions. Newton’s method is employed to solve the system of nonlinear equations governing quantum transport phenomena. The Laplace equation is used to describe the electrostatic potential, and simulations are conducted in MATLAB and R. The results provide insight into the transistor’s behavior under varying conditions, highlighting the influence of size-dependent energy levels and quantum confinement effects